Using Photovoice To Explore the Lived Environment and Experience of Older Adults With Frailty on Their Kidney Transplant Journey - Hladek, Melissa deCardi; Wilson, Deborah; Krasnansky, Katie; McDaniel, Kennedy; Shanbhag, Meera; McAdams-DeMarco, Mara; Crews, Deidra C; Brennan, Daniel C; Taylor, Janiece; Segev, Dorry; Walston, Jeremy; Xue, Qian-Li; et al. (Ovid Technologies (Wolters Kluwer Health), 2024)
BACKGROUND: Older adults with frailty and kidney failure face higher waitlist mortality and are more likely to be listed as inactive on the kidney transplant (KT) wait list. Photovoice is a qualitative participatory research method where participants use photographs to represent their environment, needs and experiences. It offers unique insight into the lived environment and experience of patients and may offer direction in how to improve functional independence, symptom burden, and kidney transplant outcomes in adults with frailty. METHODS: This photovoice study was embedded within a larger intervention adaptation project. Participants with pre-frailty or frailty awaiting a KT or recently post-transplant took photos with Polaroid cameras and wrote short descriptions for 11 prompts. Each participant completed a semi-structured interview wherein their photos were discussed. The team coded and discussed photos and interviews to determine overarching themes and implications. Focus groups were used to triangulate visual data findings. RESULTS: Sixteen participants completed both the photovoice and interview. Participants were a mean age of 60.5 years, 31.2% female, 43.4% self-identifying as Black, and 69% were frail. Outcomes were categorized into seven themes: functional space, home safety, medication management, adaptive coping, life changing nature of dialysis, support and communication. Visual data clarified and sometimes changed the interpretations of the text alone. Especially within the themes of home safety and functional space, safety hazards not previously recognized in the literature, like dialysis fluid storage, were identified. CONCLUSIONS: Photovoice contextualizes the living conditions and experiences of adults with frailty on the kidney transplant journey and could be a useful tool in geriatric nephrology and transplant. Addressing issues of home storage, organization, and accessibility should be explored as potential intervention targets. Incorporating participant values and goals into care decisions and interventional design should be further explored.
Keywords: 4203 Health Services and Systems; 42 Health Sciences; Transplantation; Clinical Research; Kidney Disease; Aging; Organ Transplantation; 7 Management of diseases and conditions; 7.1 Individual care needs; Generic health relevance; Renal and urogenital; 3202 Clinical sciences; 4202 Epidemiology